Quality and yield of yam tubers cultivated with green manure in the Northeastern Brazil - Garrido, Marlon Da Silva; Soares, Ana Cristina Fermino; Menezes, Rômulo Simões Cezar; Sampaio, Everardo Valadares de Sá Barreto; Souza, Erik Micael da Silva; Macedo, Bruno Lopes do Nascimento (Comunicata Scientiae, 2018)
Yam (Dioscorea cayennensis Lam.) is a promising crop for small growers in the Northeast of Brazil, but productivities are limited due to low fertilization rates. Green manure could be an alternative due to its low cost and high availability. However, there is little information available regarding the effects of green manures on the productivity of yam. The quality and yield of yam tubers, “da costa” variety, were evaluated under application of three different green manures and a control treatment: 1) yam intercropped with sunn hemp (Crotalaria juncea L.); 2) yam intercropped with pigeon pea (Cajanus cajan L.); 3) yam intercropped with a combination of sunn hemp and pigeon pea; and 4) conventional yam crop system. The experiment was laid out in a randomized block design, with four repetitions. The data was submitted to analysis of variance and averages compared by Tukey´s test at 5%. Percentage values were transformed into arc sen (x/100)0.5. Sunn hemp and the combination of sunn hemp with pigeon pea produced the highest green manure biomasses (3.8 and 3.6 t DM ha-1, respectively) versus 2.1 t ha-1 with the use of only pigeon pea. However, the N concentration was higher in pigeon pea than in sunn hemp (26 and 16 g kg-1). Intercropping with pigeon pea led to the highest yield for total tubers (33.1 t ha-1), for market quality (32.2 t ha-1) and standard exportation quality tubers (23.0 t ha-1).